FDG‐PET/CT in the management of lymphomas: current status and future directions. (24th July 2018) - El‐Galaly, T. C.; Villa, D.; Gormsen, L. C.; Baech, J.; Lo, A.; Cheah, C. Y.
Abstract: FDG‐PET/CT is the current state‐of‐the‐art imaging in lymphoma and plays a central role in treatment decisions. At diagnosis, accurate staging is crucial for appropriate therapy selection: FDG‐PET/CT can identify areas of lymphoma missed by CT alone and avoid under‐treatment of patients with advanced disease stage who would have been misclassified as having limited stage disease by CT. Particularly in Hodgkin lymphoma, positive interim FDG‐PET/CT scans are adversely prognostic for clinical outcomes and can inform PET‐adapted treatment strategies, but such data are less consistent in diffuse large B‐cell lymphoma. The use of quantitative FDG‐PET/CT metrics using metabolic tumour volume, possibly in combination with other biomarkers, may better define prognostic subgroups and thus facilitate better treatment selection. After chemotherapy, FDG‐PET/CT response is predictive of outcome and may identify a subgroup who benefit from consolidative radiotherapy. Novel therapies, in particular immunotherapies, exhibit different response patterns than conventional chemotherapy, which has led to modified response criteria that take into account the risk of transient pseudo‐progression. In relapsed lymphoma, FDG‐PET/CT after second‐line therapy and prior to high‐dose therapy is also strongly associated with outcome and may be used to guide intensity of salvage therapy in relapsed Hodgkin lymphoma. Currently, FDG‐PET/CT has no role in the routine follow‐up after complete metabolic response to therapy, but it remains a powerful tool for excluding relapse if patients develop clinical features suggestive of disease relapse. In conclusion, FDG‐PET/CT plays major roles in the various phases of management of lymphoma and constitutes a step towards the pursuit of personalized treatment.